Duong Thu Huong's Novel without a Name: a silent cry from Vietnam - Mani, Manimangai (Scottish Group, 2013)
Duong Thu Huong is a Vietnamese writer who lives in exile in Paris. Her works often depict the cruelty of the Communist regime in her country. Duong who was born in Thai Binh, North Vietnam is a former member of Vietnamese Communist Party where in 1967, she joined the Women’s Youth Brigade in the front lines in the war against the Americans. She spent seven years in the jungle and in the tunnels of Binh Tri Thien which was the most bombarded part of Vietnam. She was one of the three survivors out of the 40 volunteers in that group. She was also involved with the Sino-Vietnamese War in 1979. After the reunification of North and South Vietnam in 1975, she began to speak against the communist government. Thus, her works were banned. This paper intends to show the other side of human and the humanity possessed by the communists who are seldom branded as cruel and heartless by the western media. Duong Thu Huong’s Novel without a Name is another attempt to open the same window to the same view but by a pair of different hands. She makes another effort to illustrate what has been lost in Vietnam during the years of war. To transfer the message of war to her readers, she creates a variety of characters and events during the course of the story. The whole novel can be considered as a sickening shock to open the eyes of the world to the consequences of war to the people of Vietnam. This paper will show that they too are ordinary people who are caught in an unwanted situation. They are merely the victims of circumstances who are trapped by ambitious individuals who lead them astray for their own benefits and their ideology.